مرثية الوجود في قصص سناء الشعلان نماذج مختارة: The legacy of existence in the stories of Sana Al-Shaalan selected models - Al-Abboudi, M. M. Sana Jabbar; Giled, Ali Hussein (SIBAWAYH Arabic Language and Education, 2021)
تهيمن المشاعر والنوازع النفسية على ذاتنا سواء كان بوعيٍ منّا أو لاوعي، وتؤدي دورًا كبيرًا في التأثير بأفعالنا واقوالنا ، إذ تقوم بالإتيان بالتصرفات على احساسنا و مشاعرنا في صورة موحية لافتة للنظر، ومن هنا ترتبط هذه العواطف والنوازع بمجموعة من الظواهر النفسية الذاتية، بما في ذلك مزاج الشخصية وطَبعها، زد على ذلك إحساس الشخصية وسلوكها وردود أفعالها تظهر بصورة واضحة على أثر ارتباطها بالعالم الخارجي ، والبواعث والمؤثرات التي تستقبلها وتتفاعل معها.Introduction: Feelings and psychological tendencies dominate our self, whether consciously or unconsciously, and play a major role in influencing our actions and sayings, as they perform actions on our feelings and feelings in an eye-catching suggestive form, hence these emotions and tendencies are linked to a range of psychological phenomena، including the mood and character of the character, in addition to the sense of personality and behavior and reactions that are clearly manifested on the impact of its association with the outside world. And the motivations and influences that you receive and interact with. The problem of research: Those who read and meditate on the texts of Sana al-Shaalan find that the alarms adopted in their texts are not only what drives the self to feel and be affected, but also links feelings and feelings to the process of loss to put their tragic characters under the hammer of successive transformations in circumstances and events in a specific temporal and spatial space.  Research questions: The most important questions posed by the study is that if the self finds the new starting point for its thoughts and internal tendencies, do events begin to shift increasingly from sense to perception? This study reveals the personal perception of her self and other characters as a result of which.Keywords: Sensation, existence, Self, Psychological phenomena, Personality